Measurement of Antibiotic Utilization in the Internal Medicine Ward of a Tertiary Hospital in Bangladesh - Begum, T; Parveen, F; Khan, I; Ara, F; Shana, RR; Iqbal, JU (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7030 Bangladesh Medical Journal 2010, 39(2) pp.11-15